KAJIAN ASPEK PERENCANAAN PENGANGGARAN DANA DESA TAHUN 2011 DAN 2013 (STUDI KASUS DI DESA PANTI KECAMATAN SAROLANGUN KABUPATEN SAROLANGUN) - Arnila Arnila (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2016)
This research study entitled Aspevts Of Planning Budgeting Village Fund in 2011 and 2013 (in the Village Panti Of Case Studies in Sarolangun) home districts under the guidance of Hj. Paulina Lubis, SE.,M.EI. the purpose of this study was to determine the development of the Village Fund Allocation and how planning budgeting funds in the village surveyed villages. Analysis tool used is descriptive analysis kualitatif with premises using research instruments. The results of this study indicate that : (1). Acceptencce of the Allocation of Funds in the rural Village of homes decreased in the years between 2011 and 2013. The difference in the Allocation of Village Funds amountced to -12.91%. Because in that year the Village Fund Allocation does not meet the reguirements of goverment regulations. (2). Preparation of a plan of priority activities funded rural village fund allocation conducted by the village goverment and village empowerment agencies. To draw up the action plan must invoive the participation of all components in both instituted the village community and the general public trough the village-level discussion forum.